Tantangan Pariwisata pada Wilayah Perbatasan dalam Era Disrupsi Teknologi: Studi Kasus Regulasi Transportasi Online di Kota Batam, Kepulauan Riau - Cindy Andini; Dhani Akbar (Lasigo Akademia Indonesia, 2020)
One of the products of technological disruption which is currently becoming the prima donna in order to facilitate the public is an online transportation application. Payment is also made easy, namely using e Money. Until now, tourists in Batam have started relying on this application because it is considered easy and safe. This study uses descriptive qualitative methods that aim to explain the existing problems by providing answers to the problems raised. Descriptive qualitative research is a study in which the writer explains the phenomenon that is adapted to the concept and theory as supporting material for proof of writing. Even though it makes it easy and absorbs a lot of workforce, the fact that online transportation is still a controversy has caused chaos and unrest. What policies should be implemented? and how can Industry 4.0 increase competitiveness in this strategic area? The government as a regulator needs to make policies to organize the movement of this transportation so that the conducive situation desired by tourists can be realized.